Number of prior concussions predict poorer concussion care seeking in military cadets. (10th November 2021) - Schmidt, Julianne D.; Anderson, Melissa; Weber Rawlins, Michelle; Foster, Craig A.; Johnson, Brian R.; D'Lauro, Christopher
ABSTRACT: Primary objective: To determine whether concussion history predicts concussion care seeking, self-management practices, or confidence to recognize/report. Research design:Cross-sectional. Methods & procedures: 706 United States Air Force Academy (USAFA) cadets completed survey items regarding concussion history (0, 1, 2, 3+), likelihood of reporting a concussion, self-management, and confidence to recognize/report. We used multivariate ordinal and binary logistic regression models to predict responses using concussion history, sex, and race. Main outcomes & results: cadets with 1 (OR = 0.59, 95%CI:0.43–0.82), 2 (OR = 0.55, 95%CI:0.31–0.98), or 3+ (OR = 0.36, 95%CI:0.17–0.78) concussions while at USAFA had respective 41%, 45%, and 64% lower likelihood to report the concussion scenario (ref = no history, p < .001). USAFA cadets with more extensive concussion histories had higher prevalence of not seeking care for a concussion ( p < .001); more strongly endorsed self-management ( p = .001–0.010); and had greater confidence in their ability to recognize a concussion ( p = .005), but not to report ( p = .198–0.413). Conclusions: Prior concussion experiences may deter cadets from seeking medical care for future concussions. Interventions should address concussion history and clinicians should consider how the post-concussion management process might deter care seeking.